1989
DOI: 10.1161/01.str.20.4.441
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of aspirin or heparin in hospitalized patients with recent transient ischemic attacks. A pilot study.

Abstract: In a randomized pilot study we compared the efficacy of temporary anticoagulation with intravenous heparin sodium to the efficacy of aspirin in preventing cerebral infarction in hospitalized patients with recent (<7 days) transient ischemic attacks (TIAs). Fifty-five patients (33 men, 22 women) aged 36-81 (mean 62.7) years met entry criteria and agreed to participate. Symptoms prompting hospitalization were referable to the carotid distribution in 43 patients (34 hemispheric, nine retinal); 12 patients had ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…7 Its results were consistent with our data showing a high early recurrent stroke risk in symptomatic VB stenosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…7 Its results were consistent with our data showing a high early recurrent stroke risk in symptomatic VB stenosis.…”
Section: Discussionsupporting
confidence: 92%
“…8 In addition, 14 studies were identified, which only included patients with VB stenosis, without a control group with no stenosis. Two studies reported the risk of stroke in patients with extracranial vertebral artery stenosis only (see the online-only Data Supplement references I and II), 8 in intracranial VB stenosis9 (see the online-only Data Supplement references III through IX), and in 7 the risk relating to site of stenosis was unclear 2,3,7,8 (see the online-only Data Supplement references X through XII). No studies provided direct comparative data on the risk of extracranial versus intracranial stenosis in the same study population.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…66 -74 Numerous studies also have shown that the short-term risk of stroke is particularly high, with most studies finding risks exceeding 10% in 90 days. 7,13,21,[75][76][77][78][79][80][81][82][83][84] Risk is particularly high in the first few days after TIA, with most studies finding that one quarter to one half of the strokes that occur within 3 months occur within the first 2 days. 7,21,75,79,82,84,85 For example, studies in northern California and Oxfordshire found the risk of stroke in the first 24 hours after TIA to be Ϸ4%, 75,86 which is about twice the risk of myocardial infarction or death in patients presenting with acute coronary syndromes (Ϸ2% at 24 hours).…”
mentioning
confidence: 99%
“…4 In a 1978 study, 40% of patients with a single TIA had a stroke within 1 month. 5 About 10 years later, 2 studies demonstrated a 9% risk of stroke within 6 days after a TIA, 6 and a 4.4% risk at 30 days. 7 The authors of these 2 studies respectively concluded that "patients with recent TIAs are at high risk for … brain infarction" and that "[t]he risk of stroke is greater immediately after TIA, which has important implications for clinical practice."…”
mentioning
confidence: 99%
“…Robust analyses of attributable risk due to TIAs as a function of age should be the subject of future research, as should the continued search for short-term treatments to prevent stroke. 4,6 …”
mentioning
confidence: 99%